Online portfolio for midwifery student assessment and recording of clinical experiences - Thomson, Brooke; Costins, Pauline; Kuliukas, Lesley; Bradfield, Zoe (Australian College of Midwives, 2017)
Introduction: Across Australia, the healthcare industry is moving to paperless modes of documentation. The introduction of a paperless portfolio for midwifery students follows this directive and prepares students for working in a moving technological environment. Aim: Midwifery students at Curtin University have historically recorded compulsory clinical experiences (over 300) using paper templates in a written portfolio. Records were easily lost, feedback from facilitators inconsistent and the mode of documentation outdated. Innovation: The School of Nursing, Midwifery and Paramedicine purchased an online digital personalised tutoring platform for healthcare (PebblePad) in 2016. The program has been implemented to replace the written portfolio for all new-to-course students and existing students on an elective basis. The PebblePad ‘Midwifery Practice Record’ (MPR) has been specifically designed by the midwifery teaching team, so that it contains all templates for all clinical experiences, Nursing and Midwifery Board of Australia (NMBA) registration specific competencies and reflections. Students can be formatively and summatively assessed, as both preceptors and lecturers have secure access and signature capabilities. Discussion: Implementation of an online portfolio has meant sweeping changes for the students, preceptors, clinicians and industry partners. Policies and user guides have smoothed the transition. Anecdotal student feedback suggests that the MPR is accessible and easy to use, and students participate in peer teaching of subsequent cohorts. Students are also able to keep their account at no cost, for ongoing recording of professional development, which supports lifelong learning. Industry response has been positive as it matches their demands of moving to a paperless system. The online portfolio has not only meets industry demand but also allows real-time feedback, which is particularly beneficial to remote students. Conclusions and implications for practice: The development and implementation of this new technology was a steep learning curve for students, staff and industry but has resulted in positive feedback regarding formative and summative assessment and portability.